2015
DOI: 10.1155/2015/430328
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Limitations of Lab-on-a-Chip Method over Reversed-Phase High-Performance Liquid Chromatography Method in Gluten Proteins Evaluation

Abstract: RP-HPLC (reversed-phase high-performance liquid chromatography) is widely used to determine the amounts of the different gluten protein types. However, this method is time-consuming, especially at early stages of wheat breeding, when large number of samples needs to be analyzed. On the other hand, LoaC (Lab-on-a-Chip) technique has the potential for a fast, reliable, and automatable analysis of proteins. In the present study, benefits and limitations of Lab-on-a-Chip method over RP-HPLC method in gluten protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…However, the HMW-GS identification system by SDS-PAGE was shown to be time-consuming and required a large gel system to clearly separate HMW-GS. Many research groups have tried to apply the Lab-on-a-chip system for HMW-GS identification, due to the fast and effective protein separation and quantification that offers the Lab-on-a-chip electrophoresis system [31,40]. However, the latter system is not commonly used for HMW-GS identification due to particular reasons [31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the HMW-GS identification system by SDS-PAGE was shown to be time-consuming and required a large gel system to clearly separate HMW-GS. Many research groups have tried to apply the Lab-on-a-chip system for HMW-GS identification, due to the fast and effective protein separation and quantification that offers the Lab-on-a-chip electrophoresis system [31,40]. However, the latter system is not commonly used for HMW-GS identification due to particular reasons [31].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the upper marker in the standard cultivars harboring 1Dx2.2, such as Uri and Seodun, was adjusted before analyzing the HMW-GS composition (Figure 1). The recorded molecular weights of HMW-GS on Lab-on-a-chip were above 120 kDa [31]. Table 1.…”
Section: Identification Of 1ax1 and 1ax2* At The Glu-a1 Locus By Lab-mentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, specifi c composition of HMW-GS in wheat cultivars is one of the most important genetic factors that infl uence the rheological properties of dough (PAYNE et al, 1987). It has been recently demonstrated that composition and quantity of HMW-GS could be determined by Lab-on-Chip (LOC) technique (ŽIVANČEV et al, 2013;2015), whereas for accurate determination of their amounts a combined extraction -Reversed-Phase High-Performance Liquid Chromatography (RP-HPLC) procedure developed by WIESER and coworkers (1998) is still used.…”
mentioning
confidence: 99%